Liberalism with excellence - Kramer, Matthew H., 1959- (Oxford ; New York, NY : Oxford University Press, 2017)
During the past several decades, political philosophers have frequently clashed with one another over the question whether governments are morally required to remain neutral among reasonable conceptions of excellence and human flourishing. On the one hand, the book rejects the requirement of neutrality by contending that certain subsidies for the promotion of excellence in sundry areas of human endeavour can be proper and vital uses of resources by governments. Advocating such departures from the constraint of neutrality, the book presents a version of liberalism that can rightly be classified as 'perfectionist'.0On the other hand, the species of perfectionism espoused in Liberalism with Excellence diverges markedly from the theories that have usually been so classified. Indeed, much of the book assails various aspects of those theories. What is more, the aspirational perfectionism elaborated in the closing chapters of the volume is reconcilable in most key respects with a suitably amplified version of 'Rawlsianism'. Hence, by reconceiving both the perfectionist side and the neutralist side of the prevailing disputation, 'Liberalism with excellence' combines and transforms their respective insights.
Part I. Introduction -- Toward the redirection of a longstanding controversy -- Part II. Liberal neutralism -- One cheer for edificatory perfectionism: An arm's-length defense of edificatory perfectionism against some Rawlsian objections -- The illusion of neutrality: Abortion and the foundations of justice -- Too much from too little: A critique of Gerald Gaus's libertarian neutralism -- Part III. Edificatory perfectionism -- Edifactory perfectionism and the quality of freedom -- The Quidnunc mentality of edifactory perfectionism -- Part IV. Aspirational perfectionism -- Self-respect in Rawl's liberalism -- Perfectionism in the service of justice -- The implementation and import of aspirational perfectionism.
Includes bibliographical references and index.
Keywords: Liberalism